Symptoms and medical resource utilization of patients with bronchiectasis after SARS-CoV-2 infection - Wang, Jun; Ren, Jiaqi; Li, Xin; Wang, Juan; Chang, Chun; Sun, Lina; Sun, Yongchang (Frontiers in Medicine, 2024)
Background The impact of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on patients with bronchiectasis in terms of symptoms, self-management and medical resource utilization was unknown. Objective To describe the impact of infection by SARS-CoV-2 on fluctuation of symptoms, self-management and medical resource utilization of patients with bronchiectasis during the pandemic of COVID-19. Methods This was a single-center cross-sectional questionnaire study performed in Peking University Third Hospital. An online questionnaire investigation addressing the impact of SARS-CoV-2 infection on respiratory symptoms, self-management and medical resource utilization was conducted among patients with bronchiectasis during the COVID-19 surge in December 2022 in Beijing, China. Results Five hundred patients with bronchiectasis, with 285 (57%) females, and a mean (±SD) age of 57.9 ± 15.1 years, completed the telephone questionnaire. The reported prevalence of COVID-19 was 81.2% (406/500). Of the 406 COVID-19 patients, 89.2% experienced fever lasting mostly for no more than 3 days, 70.6 and 61.8% reported exacerbated cough and sputum production respectively, and 17.7% reported worsened dyspnea. Notable 37.4% of the patients with COVID-19 experienced symptoms consistent with the definition of an acute exacerbation of bronchiectasis. However, 76.6% (311/406) of the infected patients did not seek medical care but managed at home. Of the patients who visited hospitals, 26.3% (25/95) needed hospitalization and 2.1% (2/95) needed ICU admission. Multi-factors logistic regression analysis showed that younger age (p = 0.012) and not using a bronchodilator agent(p = 0.022) were independently associated with SARS-CoV-2 infection, while a history of exacerbation of bronchiectasis in the past year (p = 0.006) and daily use of expectorants (p = 0.002) were associated with emergency visit and/or hospitalization for patients with bronchiectasis after SARS-CoV-2 infection. Conclusion During the COVID-19 surge, the infection rate of SARS-CoV-2 in patients with bronchiectasis was high, and most of the patients experienced new-onset or exacerbated respiratory symptoms, but only a minority needed medical visits. Our survey results further underscore the importance of patients’ disease awareness and self-management skills during a pandemic like COVID-19.